Strategies for Using Assistive Technology to Overcome Students with Learning Disabilities and Barriers in Elementary School - Dewi Aprilia, Yesinta; Istanti Suwandayani, Beti; Kuncahyono (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The present study identifies the implementation of assistive technology in students with learning disabilities and strategies for using assistive technology to overcome learning barriers. This research is a literature review (SLR) study conducted on articles from 2013 to 2024 using the Scopus database. The data obtained was saved in *R.I.S. format and integrated into the Reference Manager (Mendeley). Furthermore, VOS-viewer software was used to see the data making the resulting information more interesting and clear. PRISMA flowchart maps the data search process, the number of abstracts screened, and the text retrieved. A total of 8 articles were accessed for this study. The results showed that teachers must be well-prepared to improve their pedagogical skills by effectively using media and learning resources to achieve the desired goals. Technology or media must adapt teaching materials to the individual needs of students. The research results are expected to provide insight into the need for strategies to overcome learning barriers in students with learning disabilities.